Double standards: the verdicts of western election observers in sub-Saharan Africa. Issue 3 (3rd April 2019) - Dodsworth, Susan
ABSTRACT: This article tests whether Western election observers apply a "double standard" to elections in sub-Saharan Africa. It demonstrates that they do: Western election observers were statistically less likely to allege that significant fraud had occurred in an election in sub-Saharan Africa, than an election of the same quality held elsewhere, throughout the period from 1991 to 2012. This discrepancy exists despite controls for other factors commonly thought to influence the verdicts of observers, such as the strategic interests of Western countries. Yet, there is variation over time. Between 1991 and 2001, the double standard is partly explained by "progress bias, " a tendency to tolerate flawed elections that improved on those held previously. From 2002 to 2012, observers' application of a double standard is much harder to explain. In that period, the analysis points to several factors that discourage Western observers from alleging fraud, including the risk of triggering electoral violence and a desire to protect relationships with strategic partners. It also identifies factors that make allegations of electoral fraud more likely, including the precedent set by past allegations of fraud and – unexpectedly – higher levels of foreign aid. None of these factors, however, account for the regional discrepancy.